Clinical Outcomes after Uncomplicated Cataract Surgery with Implantation of the Tecnis Toric Intraocular Lens - Lubiński, Wojciech (J Ophthalmol, 2016)
Purpose. To evaluate the clinical outcomes after uncomplicated cataract surgery with implantation of an aspheric toric intraocular lens (IOL) during a 6-month follow-up. Methods. Prospective study including 27 consecutive eyes of 18 patients (mean age: 66.1 ± 11.4 years) with a visually significant cataract and corneal astigmatism ≥ 0.75 D and undergoing uncomplicated cataract surgery with implantation of the Tecnis ZCT toric IOL (Abbott Medical Optics). Visual, refractive, and keratometric outcomes as well as IOL rotation were evaluated during a 6-month follow-up. At the end of the follow-up, patient satisfaction and perception of optical/visual disturbances were also evaluated using a subjective questionnaire. Results. At 6 months after surgery, mean LogMAR uncorrected (UDVA) and corrected distance visual acuity (CDVA) were 0.19 ± 0.12 and 0.14 ± 0.10, respectively. Postoperative UDVA of 20/40 or better was achieved in 92.6% of eyes. Mean refractive cylinder decreased significantly from −3.73 ± 1.96 to −1.42 ± 0.88 D (p < 0.001), while keratometric cylinder did not change significantly (p = 0.44). Mean absolute IOL rotation was 1.1 ± 2.4°, with values of more than 5° in only 2 eyes (6.9%). Mean patient satisfaction score was 9.70 ± 0.46, using a scale from 0 (not at all satisfied) to 10 (very satisfied). No postoperative optical/visual disturbances were reported. Conclusion. Cataract surgery with implantation of the Tecnis toric IOL is an effective method of refractive correction in eyes with corneal astigmatism due to the good IOL positional stability, providing high levels of patient's satisfaction.